Integrated Course for Improve Student Competencies on School Physics Laboratory Management - Raihanati Raihanati; Upik Rahma Fitri; M. Fajrin (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2017)
Abstract School Physics Laboratory Management is one of the subjects in Physics Education Study Program on FMIPA UNJ which aims to build the competence of school laboratory management for physics education students. It have been developed integrated teaching materials consisting of syllabus, One Semester (RPS) Plan, hand out, Student Activity Sheet, and Student Performance Appraisal Sheet for Laboratory Administration Competence. The development model referred to is ADDIE. Has been validation with college Lecturer Physics Education Studies Program FMIPA UNJ, with the focus of validation of syllabus and One-Semester Lecture Plan (RPS). The recommendation of peers is the use of the tools developed in the lecture process. One Semester (RPS), hand out, Student Activity Sheet, and Student Performance Appraisal Sheet have been tested against the students. Student responses to lectures were collected using a questionnaire consisting of four pieces of grain. Students appreciate 84,59, meaning very good. The effectiveness of the use of lecture tools in building student competence is very high, which obtained an average score of 91.65 very good category. The results of the experiments show that the lecture tools developed are suitable for use as teaching materials. Keywords: integrated lecturing tools, student competence, laboratory management. Abstrak Manajemen Laboratorium Fisika Sekolah merupakan salah satu mata kuliah pada Program Studi Pendidikan Fisika FMIPA UNJ yang bertujuan membangun kompetensi pengelolaan laboratorium sekolah bagi mahasiswa pendidikan fisika. Telah dikembangkan bahan ajar terpadu yang terdiri dari silabus, Rencana Perkuliahan Satu Semester (RPS), hand out,Lembar kegiatan Mahasiswa, dan Lembar Penilaian Kinerja Mahasiswa untuk kompetensi Administrasi Laboratorium. Model pengembangan yang diacu adalah ADDIE. Telah dilakukan validasi sejawat dengan Dosen Program Studi Pendidikan Fisika FMIPA UNJ, dengan focus validasi silabus dan Rencana Perkuliahan Satu Semester (RPS). Rekomendaso teman sejawat adalah penggunaan perangkat yang dikembangkan dalam proses perkuliahan. Rencana Perkuliahan Satu Semester (RPS), hand out,Lembar kegiatan Mahasiswa, dan Lembar Penilaian Kinerja Mahasiswa telah diujicoba terhadap mahasiswa. Respon mahasiswa terhadap perangkat perkuliahan dikumpulkan menggunakan angket yang terdiri dari empatbelah butir. Mahasiswa memberikan apresiasi 84,59, artinya sangat baik. Efektivitas penggunaan perangkat perkuliahan dalam membangun kompetensi mahasiswa sangat tinggi, dimana diperoleh skor rerata sebesar 91,65 kategori sangat baik. Hasil ujicoba menunjukan bahwa perangkat perkuliahan yang dikembangkan layak digunakan sebagai bahan ajar. Kata-kata Kunci: perangkat perkuliahan terpadu, kompetensi mahasiswa, pengelolaan laboratorium.